(untitled) (International Journal of Food and Nutritional Sciences, 2023)
With the hospitality industry in India taking to luxury tent design as a pivotal trend, inheritance of the cultural heritage, while keeping the promise of the modern sophistication, is helping in creating transformative customer experiences. On this article we’ll find out how innovative tent architecture, sustainable materials, and immersive aesthetics change the traditional idea of luxury accommodation. The study presents a synthesis of insights on design elements like spatial planning, indigenous motifs, and eco-friendly practices that go toward creating a unique guest experience based on iconic luxury tent properties in India. Through blending the custom of conventional craftsmanship with more present-day needs, these designs serve the needs of affluent travellers and likewise advance the preservation of culture and ecological care. The approach chosen for this study is a mixed method approach, using a combination of qualitative interviews with hospitality designers and quantitative feedback from customers. It is found that luxury tent design helps to increase the perception of exclusivity, strengthen the bond between a customer and nature, and further the elements of cultural engagement that contribute to improved customer satisfaction and loyalty. The importance of customer centricity in a design driven hospitality context is highlighted, through which design goes beyond aesthetics to provoke emotion and memory. With actionable insights for industry stakeholders, e.g., architects, hoteliers and policy makers, it innovates at the interface of design, sustainability and cultural authenticity. This is where luxury tents in the Indian hospitality industry find themselves as experiential accommodations that can cater to evolving traveller preferences and stimulates economic and environmental sustainability at the same time.